Asking Questions in English Receptive Skills Activities; Multiple Case Studies in Two Junior High Schools in Palembang - Arrofiq, Ahmad Latif; Astrid, Annisa; Desvitasari, Deta (International Journal of Innovation and Education Research, 2024)
The purpose of this study was to find the types of students' questions in listening skill activities in SMP N 16 and 30 Palembang. This study used qualitative methods in the approach of multiple case studies. Multiple case studies were a case study that used many issues or cases in one study more complete. This research focused on the eighth grade of SMP N 16 and 30 Palembang. This research used purposeful sampling by making one English teacher representing each school to the classes being taught. The participants was choosen from class 8.3 and 8.6 to obtain data, observation and interviews were used and were analysed using thematic analysis. The establishment of trustworthiness were used by the researcher that were member checking and triangulation. The results showed that there were types of questions asked by the students in class, namely (1) Lexical questions, (2) Procedural Questions, (3) Referential Questions.